Life-writing in the History of Archaeology (UCL Press, 2023)
Life-writing is a vital part of the history of archaeology, and a growing field of scholarship within the discipline. Travels and adventures of the ‘great archaeologists’ have generated centuries-worth of bestselling books that, in turn, shaped the public perception of archaeology. The lives of archaeologists are entangled with histories of museums and collections, developments in science and scholarship, and narratives of nationalism and colonialism into the present. In recent years life-writing has played an important role in the surge of new research in the history of archaeology, including ground-breaking studies of discipline formation, institutionalisation and social and intellectual networks. Sources such as diaries, wills, film and the growing body of digital records are powerful tools for highlighting the contributions of hitherto marginalised archaeological lives including many pioneering women, hired labourers and other ‘hidden hands’.